2010
DOI: 10.1016/j.bone.2009.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic pyrophosphatase induces type I collagen in osteoblasts

Abstract: Introduction The physiologic selectivity of calcification in bone tissue reflects selective co-expression by osteoblasts of fibrillar collagen I and of tissue nonspecific alkaline phosphatase (TNAP), which hydrolyzes the calcification inhibitor pyrophosphate (PPi) and generates phosphate (Pi). Humans and mice deficient in the PPi-generating ecto-enzyme NPP1 demonstrate soft tissue calcification, occurring at sites of extracellular matrix expansion. Significantly, the function in osteoblasts of cytosolic inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 54 publications
(92 reference statements)
2
34
0
Order By: Relevance
“…3, H and I). This result is consistent with a previous report that demonstrated that ENPP1 expression in calvarial osteoblastic cells influenced TNAP enzyme activity to a greater extent than TNAP mRNA expression upon treatment of cells with ascorbate (38).…”
Section: Enpp1-deficient Mc3t3e1(c4) Cells Are Defective Insupporting
confidence: 93%
See 1 more Smart Citation
“…3, H and I). This result is consistent with a previous report that demonstrated that ENPP1 expression in calvarial osteoblastic cells influenced TNAP enzyme activity to a greater extent than TNAP mRNA expression upon treatment of cells with ascorbate (38).…”
Section: Enpp1-deficient Mc3t3e1(c4) Cells Are Defective Insupporting
confidence: 93%
“…These results indicate that the increased levels of osteoblastic gene expression seen in pPGS/ Enpp1 cells upon ascorbate treatment are not due to increased collagen expression in the pPGS/Enpp1 cells. That Col1a1 mRNA expression is increased in Enpp1 shRNA-expressing cells and decreased in Enpp1 cDNA-expressing cells is consistent with the previous report that type I collagen expression and synthesis is increased in calvarial osteoblasts isolated from Enpp1 Ϫ/Ϫ mice (38). In support of our findings that Enpp1 enhances osteoblast differentiation, pPGS control and ENPP1-overexpressing cells were generated on two separate occasions, and results were similar with both sets of cells (data not shown).…”
Section: Enpp1-deficient Mc3t3e1(c4) Cells Are Defective Insupporting
confidence: 92%
“…However, this seems to be a simplification, as there are at least two more phosphatases known to be active at the site of mineralization. PHOSPHO 1 generates Pi from phospholipids [47] and inorganic pyrophosphatase generates Pi from cytosolic PPi in osteoblasts [48]. This latter pyrophosphatase was also found to significantly regulate collagen expression.…”
Section: Phosphatementioning
confidence: 96%
“…5D). It has been reported that Opn is up-regulated upon TNAP deficiency and by increased PP i levels (14,50); therefore, we analyzed expression of a PP i transporter Ank but detected no significant difference in Ank expression between Trps1-KD cells and controls (Fig. 5E).…”
Section: Up-regulation Of Trps1 In Differentiated Odontoblastic Cellsmentioning
confidence: 99%